What Else besides War: Deliberate Metaphors Framing COVID-19 in Chinese Online Newspaper Editorials. (3rd April 2022) - Zhang, Cun; Lin, Zhengjun; Jin, Shengxi
ABSTRACT: Through metaphor, we gain distinctive perspectives on reality and communicate in new ways, especially when we use metaphor intentionally. The COVID-19 pandemic broke out in early 2020, causing significant harm to people's lives worldwide. This article moves the focus from the ubiquitous war metaphor used in the pandemic to other deliberate metaphors identified in five Chinese news media, i.e., China Daily, People's Daily, Huanqiu, Cankaoxiaoxi, and Xinhuanet . 59 Chinese online newspaper editorials were collected between 22 January 2020 and 22 July 2020. Using quantitative and qualitative methods, we investigate season, disease and medicine, and homework metaphors. We contend that (a) originating from common bodily experiences in the physical environment, season metaphors have emotional valences and promoted public confidence when the epidemic was severe and urged caution when it was mitigated, (b) connecting physical and socio-cultural worlds, disease and medicine metaphors could simplify and evaluate social issues besides formulating editorials' political stances, and (c) based on shared socio-cultural knowledge, homework metaphors call for more democratic and practical governance in disease control. This study reveals how these metaphors accomplish useful pragmatic purposes in the pandemic in particular contexts.